Sonhos dos imigrantes italianos e os caminhos de esperança : distrito de São Pedro, Bento Gonçalves - RS - Zat, Ancilla Dall`Onder (My University, 2023)
The italian immigration in Bento Gonçalves - Rio Grande do Sul has been the subject of several studies and researches from diferent perspectives. This dissertativo, linked to the Graduate Program in History at the University of Caxias do Sul, focuses on the study of Italian immigration in the district of São Pedro, centered on the immigration legary and its valuation by the descendants and residents or the place. The objetive was to analyze the immigration process and its relationship with the development of São Pedro Discrict in the perception of its residents. In its methodology, the study is descripte in nature with qualitative approach and follow a the principles of oral history. It makes a brief literature review dialoguing with diferente authors of the conceptual assemptions of Accorsi, Luchese And Santos (1997), Heredia (2015), Caprara and Luchese (2005), Dall'Agnol (2004), Gasperin (2000), Nora (1993), Candau (2012), Farina (2022) and Portelli (2016) among others, and the speeches of the interlocutors. Were realized interviews with five residentes of São Pedro District and two wich descendants selected by inheritance or property purchase, it allowed the analysis of the results to understand the evaluative perceptions in the identity memories of the respondents that shows recognition to the immigration legacy and the current role of economic development of the locality. As a common point among the intervivences and research resulto f the investigation, the recognition of improved financial and life quality of local families with tourism and knowledge and ways of living that were inherited from ancestors. As for the final product, the research produced an illustrated album with the perceptions of the participants to be distributed to the interviewees, to the "Caminhos de Pedra" Association and to the schools located throughout the District. [resumo fornecido pelo autor]
A imigração italiana em Bento Gonçalves, Rio Grande do Sul, tem sido tema de vários estudos e pesquisas em diferentes perspectivas. Esta dissertação, vinculada ao Programa de Pós-Graduação em História da Universidade de Caxias do Sul, focaliza o estudo na imigração italiana no distrito de São Pedro, centralizado no legado imigratório e sua valorização pelos descendentes e moradores da localidade. Objetivou-se analisar o processo imigratório e sua relação com o desenvolvimento do Distrito de São Pedro na percepção dos seus moradores. Em sua metodologia, o estudo é de caráter descritivo com abordagem qualitativa e segue os princípios da história oral. Faz uma breve revisão de literatura dialogando com diferentes autores dos pressupostos conceituais de Accorsi, Luchese e Santos (1997), Herédia (2015), Caprara e Luchese (2005), Dall'Agnol (2004), Gasperin (2000), Nora (1993), Candau (2012), Farina (2022) e Portelli (2016), entre outros, e as falas dos interlocutores. Foram realizadas cinco entrevistas com moradores de São Pedro e duas com descendentes selecionados por herança e/ou compra da propriedade permitiu a análise dos resultados para conhecer as percepções valorativas nas memórias identitárias dos respondentes que sinalizam reconhecimento ao legado imigratório e ao protagonismo do atual desenvolvimento econômico da localidade atual. Como ponto comum entre os entrevistados e resultado da investigação, o reconhecimento da melhoria na qualidade financeira e de vida das famílias da localidade com o turismo e com os saberes e os modos de viver que foram herdados dos antepassados. Quanto ao produto final a pesquisa produziu um álbum ilustrado com as percepções dos participantes a ser distribuído aos entrevistados, à Associação "Caminhos de Pedra"e às escolas situadas ao longo do Distrito. [resumo fornecido pelo autor]
Keywords: Italianos - Bento Gonçalves (RS) - História; Imigração - Itália - Bento Gonçalves (RS); História - Estudo e ensino; Italians - Bento Gonçalves (Brazil) - History; Emigration and immigration - Italy - Bento Gonçalves (Brazil); History - Study and teaching